Marketing Mixes Influencing the Decision Making in Choosing the Accommodation of Nakhon Pathom Rajabhat University Students - Chatchawanchanchanakij, Petcharaporn; Subongkod, Mallika; Arphonpisan, Pannarat (Asian Administration and Management Review, 2019)
The objectives of this research are 1) to study the marketing mixes and the decision making in choosing the accommodation of Nakhon Pathom Rajabhat University students and 2) to study the marketing mixes influencing the decision making in choosing the accommodation of Nakhon Pathom Rajabhat University students. The sample group consists of 260 students. The convenience sampling is used for random sampling. The data is analyzed by using the descriptive statistics, percentage, mean, standard deviation, and inferential statistics. The correlative statistical analysis is used between the independent variables and dependent variables and the hypotheses are tested using the structural equation analysis having the values used for checking the harmony and the corresponding values of the structural equation model with empirical data. The research results reveal as follows. Most of the respondents are female calculated as 51.5% having the ages between 20-25 years calculated as 57.0%. Most of them have the education level in the bachelor’s degree for 70.5%. They are studying in the Faculty of Management Science calculated as 30.5%. They have the single status calculated as 72.5%. The levels of opinions about the marketing mixes and the decision making in choosing the dormitory of Nakhon Pathom Rajabhat University students are found in the high level ( X = 4.34). The results of the analysis have the component values of 0.88, 0.85, 0.84, 0.83, 0.82, 0.64 and 0.50, respectively. The results of hypothesis test have the route coefficient equaling to 0.88 with statistical significance at the 0.01 level.